Narrow-band phototherapy in the treatment of atopic dermatitis: mechanisms of action, methodology of implementation - Maryanna B. Zhilova; Pavel V. Gorodnichev (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Phototherapy is widely used to treat various chronic skin diseases. One of the most effective methods of treatment is narrow-band medium-wave ultraviolet radiation with a wavelength of 311 nm (UVB-311). UVB-311 is used for such immune-mediated diseases as atopic dermatitis, psoriasis, vitiligo, mycosis fungoides and others. Despite the fact that the method was developed more than 30 years ago, the exact mechanism of its therapeutic action remains insufficiently studied. To date, most of the effects of UVB-311 are explained by its effect on the immune cells of the skin. This review examines data on the effects on the main molecular targets, including T-lymphocytes, keratinocytes, Langerhans cells, cytokine profile, epidermal barrier proteins. Data on the features of the pathogenetic effect of UVB-311 on the immune mechanisms of pathogenesis in atopic dermatitis were obtained. The issues of dosing by determining the minimum erythemic dose (MED) or skin phototype, methodology of procedures are discussed. Prospects for further study of photobiological aspects of UVB-311 action are determined.